2011
DOI: 10.1096/fj.10-174433
|View full text |Cite
|
Sign up to set email alerts
|

Membrane‐tethered peptides patterned after the TRP domain (TRPducins) selectively inhibit TRPV1 channel activity

Abstract: The transient receptor potential vanilloid 1 (TRPV1) channel is a thermosensory receptor implicated in diverse physiological and pathological processes. The TRP domain, a highly conserved region in the C terminus adjacent to the internal channel gate, is critical for subunit tetramerization and channel gating. Here, we show that cell-penetrating, membrane-anchored peptides patterned after this protein domain are moderate and selective TRPV1 antagonists both in vitro and in vivo, blocking receptor activity in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 42 publications
(77 reference statements)
1
35
0
Order By: Relevance
“…Our data also suggest that the strong inhibition of the TRPV3 current at highly acidic pH levels may not be accounted for by simple conductance inhibition, indicating that an inhibitory effect of proton on channel gating may also exist. A second pH sensing domain or general charge effects on the TRP domain may contribute to this inhibition (82).…”
Section: Discussionmentioning
confidence: 99%
“…Our data also suggest that the strong inhibition of the TRPV3 current at highly acidic pH levels may not be accounted for by simple conductance inhibition, indicating that an inhibitory effect of proton on channel gating may also exist. A second pH sensing domain or general charge effects on the TRP domain may contribute to this inhibition (82).…”
Section: Discussionmentioning
confidence: 99%
“…TRPV1 TRPducins selectively inhibits TRPV1 over other TRPV channels and can block heat-, acid-, and voltage-evoked TRPV1 currents. This process inhibits CGRP release from cultured neurons and lowers chemically-but not mechanicallyinduced pain (Valente et al, 2011). Similarly, small PKC sequence peptides fused to membrane-permeating TAT sequences can selectively inhibit specific PKC isoforms and have been shown to reduce ischemic heart damage (Chen et al, 2001).…”
Section: Therapeutic Targeting Of G Protein-coupled Receptor-transmentioning
confidence: 99%
“…Molecular Model Building-The molecular model for TRPM8 was modeled using the structures of the TRPV1 ion channel in the closed (Protein Data Bank code 3J5P) and open state (Protein Data Bank code 3J5R) determined by electron microscopy at 3.4-Å resolution (28). Sequence alignment between rat TRPV1 and TRPM8 was performed with ClustalO (30) from the European Bioinformatic Institute (EBI).…”
Section: Sds-page Electrophoresis and Westernmentioning
confidence: 99%
“…A recent study in TRPV1 has shown that the TRP domain is primarily involved in the allosteric activation of the gate of the channel (27). Noteworthy, a peptide patterned after the TRP domain of TRPV1 selectively blocked TRPV1 activity (28), supporting the tenet that the TRP domain is involved in protein-protein interactions that are central for coupling stimuli sensing to gating (15). Moreover, in TRPM8, the TRP domain appears directly involved in phosphatidylinositol 4,5-bisphosphate-mediated regulation (12).…”
mentioning
confidence: 99%